2007
DOI: 10.4028/www.scientific.net/ssp.121-123.495
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immobilization of Streptavidin on Mixed Self-Assembled Monolayers as Mixing Ratio

Abstract: We report on the distribution of mixed self-assembled monolayers (SAMs) composed of biotinylated and diluent alkylthiolates for streptavidin immobilization. Two thiol derivatives, 11-mercapto-1-undecanol (MUOH) and 11-mercaptoundecanoic-(8-biotinylamido-3,6-dioxaoctyl) amide (MBDA), were employed for mixed SAM. These thiols formed self-assembled monolayer without local domain, and streptavidins were immobilized onto biotinylated gold surface without nonspecific binding. In order to find the optimized condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Even though fundamental studies involving OEG-based monolayers have been reported as early as 1991 by Prime and Whitesides, related applications only began in the past decade. Alkanethiols with terminal carboxylate (−COOH) groups have been widely used in pure or mixed monolayers, and OEG-based alkylthiolates (SH–(CH 2 ) m –EG n COOH) have been recently characterized for biosensing purposes. Mixed SAMs based on linear alkanethiols with small molecular variations in termini have been studied for biosensing and other applications. Recently, studies have been carried out with mixed OEG-based alkanethiol monolayers. ,,, The structure and properties of the mixed monolayers have an effect on the ligand immobilization and, in turn, on subsequent sensing properties. Properties of sets of mixed monolayers will not be necessarily similar when the terminal functional groups are changed .…”
Section: Introductionmentioning
confidence: 99%
“…Even though fundamental studies involving OEG-based monolayers have been reported as early as 1991 by Prime and Whitesides, related applications only began in the past decade. Alkanethiols with terminal carboxylate (−COOH) groups have been widely used in pure or mixed monolayers, and OEG-based alkylthiolates (SH–(CH 2 ) m –EG n COOH) have been recently characterized for biosensing purposes. Mixed SAMs based on linear alkanethiols with small molecular variations in termini have been studied for biosensing and other applications. Recently, studies have been carried out with mixed OEG-based alkanethiol monolayers. ,,, The structure and properties of the mixed monolayers have an effect on the ligand immobilization and, in turn, on subsequent sensing properties. Properties of sets of mixed monolayers will not be necessarily similar when the terminal functional groups are changed .…”
Section: Introductionmentioning
confidence: 99%